Why do patients with lupus nephritis die?. Issue 6462 (12th January 1985) - Correia, P; Cameron, J S; Lian, J D; Hicks, J; Ogg, C S; Williams, D G; Chantler, C; Haycock, D G
Abstract : Over 20 years 42 of 138 patients with systemic lupus erythematosus "died"--that is, suffered actual death or went into terminal renal failure, or both; data from 41 were available for analysis. In most patients the causes of death were multiple. Twenty seven patients went into terminal renal failure, of whom 25 were offered dialysis treatment. Three regained renal function later, 12 survived on dialysis or with functioning kidney allografts--almost all with inactive lupus--but 13 died after starting dialysis, most within a few weeks or months. The principal causes were active lupus or infection. In those patients with renal failure after rapid deterioration in renal function (n = 14) there were nine deaths, while of 10 patients with a slow evolution into renal failure, only four died. Four patients with impaired and 10 with normal renal function died, again most often from complications of lupus or from infection. Vascular disease was a major cause of death in seven patients, all but two of whom were young; of 15 postmortem examinations, eight showed severe coronary artery atheroma, and three surviving patients required coronary bypass operations. Analysis of the timing of death or entry into renal failure showed that in 12 out of 13 patients who died within two years of onset the lupus was judged to be active, while this was true in only eight out of 19 patients who died later. Six of the seven vascular deaths occurred later than two years from onset, while only nine of 26 renal "deaths" occurred before two years; deaths from infections (n = 13) were distributed equally. Despite this and aggressive treatment of active disease, the principal cause of actual death was uncontrolled lupus.